The Fate of Angiotensin II in Placental Tissue and Blood - Mizutani, Shigehiko; Mizutani, Hidesuke; Mizutani, Eita; Arita, Harumasa; Kajiyama, Hiroaki (Hormone and Metabolic Research, 2023)
The existence of a non-canonical pathway of renin-angiotensin system in the blood pressure control system has been highlighted over the past three decades. The enzymes involved in this pathway include a series of angiotensinases such as neprilysin (NEP), aminopeptidase A (APA), carboxypeptidase, and angiotensin converting enzyme 2. The physiological roles of these peptidases have been reconsidered in this study, based on the publications of other research groups and the results from our previous study, regarding the liberation of constituent amino acids from angiotensin II by placenta tissue and blood serum, respectively.
Keywords: pregnancy; hypertension; renin-angiotensin system; neprilysin; aminopeptidase A; angiotensin convertingenzyme